The Effects of Probiotic Supplementation on Opioid-Related Disorder in Patients under Methadone Maintenance Treatment Programs. (30th March 2022) - Molavi, Nader; Rasouli-Azad, Morad; Mirzaei, Hamed; Matini, Amir Hassan; Banafshe, Hamid Reza; Valiollahzadeh, Marjan; Hassanzadeh, Majid; Saghazade, Ahmad Reza; Abbaszadeh-Mashkani, Samira; Mamsharifi, Peyman; Ghaderi, Amir
Abstract : Introduction . Patients under methadone maintenance treatment programs (MMTPs) are susceptible to numerous complications (e.g., mental and metabolic disorders). This study evaluated the effects of probiotics on clinical symptoms, biomarkers of oxidative stress, inflammation, insulin resistance, and serum lipid content in patients receiving MMTPs. Materials and Methods . A randomized, double-blind, placebo-controlled trial was conducted among 70 patients receiving MMTPs to receive either 1.8 × 10 9 CFU/day probiotics ( n = 35) or placebo ( n = 35) for 12 weeks. Clinical symptoms and metabolic profiles were measured before and after the intervention in patients receiving MMTPs. Results . Compared with the placebo group, probiotic supplementation resulted in a significant improvement in the severity of depression (P < 0.05 ). In addition, probiotic administration significantly decreased fasting plasma glucose (FPG), total cholesterol, and low-density lipoprotein cholesterol (LDL cholesterol) (P < 0.05 ). Furthermore, probiotics resulted in a significant reduction in high-sensitivity C-reactive protein (hs-CRP) and a significant elevation in total antioxidant capacity (TAC) and total glutathione (GSH) levels (P < 0.05 ). Conclusion . Treatment with probiotics for 12 weeks to patients receiving MMTPs had beneficial effects on symptoms of depression, as well as several metabolic profiles. Clinical Trial Registration: this study was registered in the Iranian website (https://www.irct.ir ) for clinical trials registration (https://fa.irct.ir/trial/46363/IRCT20170420033551N9 ). The registration date is March 22, 2020.